Evaluation of ecological security and ecological maintenance based on pressure-state-response (PSR) model, case study: Fuzhou city, China. Issue 7 (9th August 2022) - Lai, Shuhui; Sha, Jinming; Eladawy, Ahmed; Li, Xiaomei; Wang, Jinliang; Kurbanov, Eldar; Lin, Zejing; Wu, Longbin; Han, Run; Su, Yung-Chih
Abstract: Since the modern industrial revolution, the speed of urbanization has accelerated, resulting in a series of ecological environment problems. Fujian province will begin to implement the policy of strengthening the provincial capital in October 2021. Therefore, it is crucial to analyze the ecological maintenance status of Fuzhou and provide a relevant reference for Fuzhou to be built into a national central city. This article takes Fuzhou city as the research area, collects land use data in 2000, 2010, and 2020 from Globeland30, combines remote sensing image data, statistical yearbook data, and Digital Elevation Model (DEM) data, and based on Pressure-State-Responses (PSR) model. A total of 15 indicators were selected to construct the ecological security evaluation system of Fuzhou in 2000, 2010, and 2020, and the weight of each indicator was determined by analytic hierarchy process. Spatial autocorrelation was used to analyze the correlation degree of the land use ecological security index in Fuzhou. The concept of ecological maintenance was introduced to analyze the status of ecological maintenance in Fuzhou during the third period. Finally, the diagnostic model of obstacle factors was used to determine the main obstacle factors affecting ecological security in Fuzhou. The results showed that from 2000 to 2020, the area of cultivated land, grassland and bare land decreased year by year, and transferred 320.63 km 2, 25.34 km 2 and 9.85 km 2 to the artificial surface respectively. The high-value ecological security indexes in 2000, 2010 and 2020 were 27.54%, 28.67% and 30.93% respectively. Therefore, the overall level of ecological security in Fuzhou has improved, but there is a large gap in local ecological security. The area with moderate ecological maintenance degree accounted for 60.15%. From the perspective of the whole city, the very poor ecological maintenance degree mainly concentrated in the downtown area and Pingtan Island, while the very good ecological maintenance degree accounted for very little, mainly distributed in the northwest of Fuzhou. The ecological security index showed the characteristics of high and low-value agglomeration, and the distribution of four clusters in three periods was similar. The main obstacle factors of ecological security in three periods are highway density, population density, surface temperature, intensity of human interference, landscape diversity, GDP per capita, and regional development degree. The ecological security evaluation and ecological maintenance of Fuzhou city is beneficial to provide an efficient decision support tool for the ecological environment protection of Fuzhou City.